Exploring multi-party interaction in tv talk show: non-verbal as resources for cooperative interruption - Mohd Azalan, Aida Sahira; Abdullah, Nur Nabilah (2019)
Interruption in conversation does not necessarily have to be negative as it could also be viewed as something positive such as for maintaining and progressing a conversation (Amalia, 2016; Li, 2001). This paper explored interruption practices in a Malaysian television (TV) talk show called the DOPStv (Deen of Peace Studios), an Islamic lifestyle talk show. The data was collected from the online YouTube videos in which the series on ‘couple talk’ was selected as the TV talk show represented a multi-party interaction where more than two speakers were involved in the talk. Using the conversation analysis approach, this study analyzed how interruption was managed by the participants in the TV talk show. The findings suggested that the participants in the DOPStv talk show utilized the use of non-verbal cues as resources for cooperative interruption such as to provide assistance, agreement and clarification in a multi-party interaction.